Reinterpretacja okoliczności zwiadu w Kanaanie (Lb 13-14) w tekstach Filona z Aleksandrii (Mos. 1,220-236) i Józefa Flawiusza (Ant 3,300-316) - Mateusz Wyrzykowski (Warszawskie Studia Teologiczne)
The article aims to present and analyze the reinterpretation of the circumstances of the reconnaissance in Canaan in the texts of De vita Moysis Philo of Alexandria and Antiquitates Judaicae by Joseph Flavius. The text focuses on the theft of fruit from land that Moses did not own. Later authors tried to present the story in such a way that the leader of the nation would not be accused of theft. Philo describes Moses as the leader and ruler of the armies. Josephus Flavius shows the significant role of the people in leaving the borders of Canaan